Respuesta :
Answer:
[tex] \frac{ay}{x} - dx = wx [/tex]
multiply x through out:
[tex]ay - {dx}^{2} = w {x}^{2} \\ {wx}^{2} + {dx}^{2} = ay[/tex]
factorise out x²:
[tex] {x}^{2} (w + d) = ay \\ {x}^{2} = \frac{ay}{w + d} [/tex]
take square root on both sides:
[tex] \sqrt{ {x}^{2} } = \sqrt{ \frac{ay}{w + d} } \\ \\ x = \sqrt{ \frac{ay}{w + d} } [/tex]
Step-by-step explanation:
the biggest obstacle is usually a division by x.
so, let's get rid of it by multiplying both sides of the equation by x
ay - dx² = wx²
then
ay = wx² + dx² = (w+d)x²
y = (w+d)x²/a = x² × (w+d)/a